Karatsuba Ofman Multiplication Implementation on SystemC for Diffie-Hellman Key Exchange Algorithm - Aygun, Sercan; Kouhalvandi, Lida; Ors, Berna; Gunes, Ece Olcay (IEEE, 2017)
As technology develops, there becomes the huge needing for cryptologic approaches for data security. Especially for communication between devices/systems, it is needed some protocols to be handled reliably. In today's VLSI systems, it is forecasted to obtain devices with less size, less cost, and less power consumption for future applications. Thus, there arise two basic points, one is about the security and the other is about the power. Cryptography can require computationally hard calculations, so power consumption creates the tradeoff. Then, it turns out to concentrate on the new algorithmic approaches for these numerical calculations which can reduce their complexity. This paper basically aims to design a system with SystemC to handle the Diffie Hellman Key Exchange approach in hardware. There is going to be the implementation of the modular exponentiation using Karatsuba Ofman Multiplication algorithm. The objective is to design a system both with hardware and software structure. Throughout that paper, the design is going to be tested by showing the analysis in console based interface.
Keywords: cryptography; Diffie-Hellman key exchange; hardware descriptive languages; Karatsuba Ofman; multiplication algorithm; secure communication; SystemC; Computer Science; Engineering